Thin layer drying characteristics and its influence on the physical properties and bioactive compounds of misai kucing plant (orthosiphon staminues) leaves - Sriyana Abdullah author (School of Bioprocess Engineering, University Malaysia Perlis, 2015)
In this study, a thin layer techniques was used to dry Orthosiphon stamineus. Moisture sorption behaviour, drying kinetics and effects of drying conditions on final quality of Orthosiphon stamineus leaves were investigated. Adequate knowledge of the drying characteristics provides appropriate final samples mlisture content, thus decreases drying time, mass losses, risk of quality degradation, and reduces energy consumptions.